Effects of Mesobiliverdin IXα-Enriched Microalgae Feed on Gut Health and Microbiota of Broilers - Chang, Cheng-Wei T.; Takemoto, Jon Y.; Chang, Pei-En; AlFindee, Madher N.; Lin, Yuan-Yu (Frontiers in Veterinary Science, 2021)
Gut inflammatory bowel diseases (IBDs) and links to animal medicinal feed and antibiotic-resistance are fueling major economic impacts in the agricultural livestock industry. New animal feeds that promote livestock gut health and control of IBDs without antibiotics are needed. This study investigates the effects of mesobiliverdin IX(MBV)-enriched microalgae spirulina extracts on the growth performance, blood parameters, intestinal morphology and gut microbiota of broilers. A total of 288 one-day-old broiler chicks (Arbor Acres) were randomly allotted to 6 dietary treatments (four pens/treatment and 12 birds/pen). The dietary treatments comprised a basal diet as control (CON), basal diet plus 0.05% and 0.1% microalgae extract as low and high dose respectively (SP1 and SP2), basal diet plus 0.05% and 0.1% MBV-enriched microalgae extract as low and high dose respectively (MBV-SP1 and MBV-SP2), and basal diet plus 0.1 % amoxicillin (AMX). All treated animals showed no significant differences in live weight, average daily gain and feed efficiency compared to control animals. Histological examination showed that AMX treatment decreased the villi lengths of the duodenum and ileum below control villi length (P < 0.05) while MBV-SP1 and particularly MBV-SP2 increased villi lengths in the duodenum, jejunum and ileum above AMX -treatment lengths (P < 0.05). The Firmicutes/Bacteroidetes ratio increased in the cecum of broilers fed AMX (P < 0.05) while SP2, MBV-SP1 and MBV-SP2-fed animals showed (in order) increasing ratios up to the AMX level. The abundance of bacterial species of the genus Lactobacillus increased in MBV-SP1 and MBV-SP2-fed groups including a striking increase in Lactobacillus salivarius abundance with MBV(H) (P < 0.05). Feeding MBV-SP1 and MBV-SP2 decreased the level of pro-inflammatory cytokine IL-6 in plasma of broilers to a greater extent than SP1 and SP2. These results reveal that MBV-enriched microalgae extracts improve the intestinal health and beneficial microflora composition of broilers.